PERANCANGAN PROMOSI HOTEL GARUDA PADANG MELALUI MEDIA WEBSITE - BOY HARDI KUMARA, Drs. Ariusmedi, M.Sn., Yofita sandra, S.Pd., M.Pd. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
In the modern world of this hotel we have encountered many in particular in the city of Padang, the number of hotels is because most people travel far from their homes either for business or just go on holiday with family and friends, thus from various types of hotels in Padang city of course they have advantages and attractiveness of each in terms of design, facilities and in terms of service, so that the audience want to use the services they offer, where the purpose of the hotel is to gain profit and convenience. The purpose to provide satisfaction and comfort for the audience. The Garuda Hotel Company seeks to promote services that are expected to reach a broader target, for it needs a media campaign, which is a media used by companies to inform the public about the services offered so that the promotional media can be used in accordance with expectations. The results to be achieved is designing Garuda Hotel web design in Padang city that is easy to understand and understood by the target audience so that the message can be delivered to the target audience.Keywords : Designing, Web Design, Promotion, Hotel Garuda.